China Hebei province energy enterprises datasetMendeley Data - MA Dongliang; Yang Hui (Data in Brief, 2025)
This article presents a distributional summary dataset of energy enterprise firms. Nearly 9180 energy business firms distributed within various regional boundaries in Hebei Province of China are described. It includes information on energy companies established from January 1, 1958 to August 8, 2019. Specifically, it includes six types of characteristic variables such as the county region where they are located, industry classification, registered capital, enterprise type, enterprise status, and establishment time. Since this is a real dataset of business registrations, all data elements related to the real company name and legal representative of the business are removed. Due to the scarcity of real business data for scientific and educational purposes, these datasets play an important role in research and education in new energy economic analysis, spatial geographic characterization, machine learning or data mining.